CMOS sensor‐based palm‐sized in‐line optical analysis device for microchemistry systems. Issue 17 (1st August 2014) - Tokuda, T.; Wakama, N.; Terao, K.; Masuda, K.; Mori, R.; Noda, T.; Sasagawa, K.; Nishiyama, Y.; Kakiuchi, K.; Ohta, J.
Abstract : A palm‐sized optical measurement device capable of polarisation rotation and single‐wavelength absorption measurements is presented. The device is equipped with a polarisation‐analysing CMOS image sensor with an on‐chip multi‐angular polariser array. The volume of the device is as small as 51 cm 3, which is smaller than both 1/1000 of a conventional desktop polarimeter and 1/10 of the previous device. The capability of the proposed device to perform simultaneous polarisation rotation/single‐wavelength absorption measurements is experimentally verified through in situ monitoring of a photochemical reaction performed in a microflow reactor.